Characterization of a short, cis-acting DNA sequence which conveys cell cycle stage-dependent transcription in Saccharomyces cerevisiae. - McIntosh, E M (1991)
Comparison of the 5'-flanking regions of several cell cycle-regulated DNA replication genes of Saccharomyces cerevisiae has revealed the presence of a common sequence, 5'-ACGCGT-3', which is upstream and proximal to mapped transcription initiation sites. This sequence, which is the cleavage site for the restriction endonuclease MluI, is present twice in the upstream region of the yeast thymidylate synthase gene TMP1. Previous studies have implicated these MluI sites as critical components in the cell cycle-dependent transcription of TMP1. In this study, we examined more closely the importance of the ACGCGT sequences for the transcription of this gene. Using site-directed mutagenesis in combination with deletion analysis and subcloning experiments, we found that (i) while both of the TMP1 MluI sites contribute to the total transcription of this gene, the distal site is predominant and (ii) the 9-bp sequence ACGCGTTAA encompassing the distal MluI site exhibits properties of a cell cycle-stage dependent upstream activation sequence element. The results of this study support the notion that the ACGCGT sequence is an integral component of a transcription system which coordinates the cell cycle-dependent expression of DNA replication genes in S. cerevisiae.